PHYTOCHEMICALS AND ANTIOXIDANT STUDIES OF THE METHANOL FRUIT EXTRACT OF Morinda citrifolia L. (Rubiaceae) - U. M. JAJERE; M. MUSA; Y.A. RABIU; H.M. IBRAHIM; V. ATINGA; T. L. MUSA; I. SABO; T.C. SAMAGORO; U. A. YAKUBU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The fruits extract of Morinda citrifolia (Noni) has been used widely as a complementary and alternative therapy in many countries owing to its potent antioxidant activity and proven health benefits. Traditionally, it has been used as a therapeutic remedy to various diseases such as antibacterial, antitumor, antihelminthics, analgesic, anti-inflammatory, immunostimulant. This study is designed to evaluate the phytochemicals and antioxidants properties of the extract of M. citrifolia L. (Rubiaceae). 2,2,-diphenyl-1-picrylhydrazyl (DPPH) Assay was carried out to determine the reducing/scavenging power of the fruit extract against DPPH free radicals in comparison to standard antioxidant (Ascorbic acid). The qualitative phytochemical screening of the methanol fruit extract showed the presence of tannins, triterpene/steroids, carbohydrates, glycosides, saponins, flavonoids while alkaloids and anthraquinones were found to be absent. Thin layer chromatographic analysis confirmed the presence of some chemical constituents in the extract. The highest absorbance was observed for standard antioxidant (Ascorbic acid) with 96.11nm in comparison to M. citrifolia with highest absorbance of (55.35nm) at 0.5mg/ml of both standard drug and sample extract. A paired sample test showing a mean variation of 44.49nm between the standard antioxidant (Vitamin C) radical scavenging activities (RSA) and the fruit extract of M. citrifolia indicating a significant differences at P<0.05 i.e. 95% confidence interval. Thus, the fruit of the M. citrifolia can be used as a potential source of antioxidants for preventive and curative purpose against metabolic diseases.